An analysis of prehospital care for victims of accidents and violence in recife, brazil (2010)
Objectives This study was aimed at carrying out a situational diagnosis of the prehospital healthcare network for victims of accidents and violence in Recife, Brazil. Methods National policy for reducing accident- and violence-related morbidity and mortality was used as reference. Questionnaires were applied and half-structured interviews conducted with managers and healthworkers from thirteen prehospital fixed units and one mobile unit. Results Children, adolescents and females predominantly sought attention; there were few preventative actions, little social coverage and deficient referral, counter-referral and communication with other sectors. A lack of equipment and basic materials, insufficient multidisciplinary teams and the need for ongoing training were also observed. Notifying and recording accidents and violence also lacked precision; ensuring that these were done properly would allow track to be kept of them as well as developing a proper assessment and action plan. However, important state, city and academic initiatives towards preventing and reducing morbidity and mortality caused by accidents and violence in particular municipalities were identified. Conclusions Taking national policy for reducing accident- and violence-related morbidity and mortality as a point of reference, then it can be seen that some advances have been made in the city of Recife; however, many shortcomings can still be seen in terms of introducing such policy.